Behavioral fever in ectothermic vertebrates. (January 2017) - Rakus, Krzysztof; Ronsmans, Maygane; Vanderplasschen, Alain
Abstract: Fever is an evolutionary conserved defense mechanism which is present in both endothermic and ectothermic vertebrates. Ectotherms in response to infection can increase their body temperature by moving to warmer places. This process is known as behavioral fever. In this review, we summarize the current knowledge on the mechanisms of induction of fever in mammals. We further discuss the evolutionary conserved mechanisms existing between fever of mammals and behavioral fever of ectothermic vertebrates. Finally, the experimental evidences supporting an adaptive value of behavioral fever expressed by ectothermic vertebrates are summarized. Highlights: Behavioral fever in ectotherms and fever in endotherms are evolutionary related responses to infections. The homology between the regulation pathways of behavioral fever and fever exists at the level of the central nervous system. Evidences supporting an adaptive value of behavioral fever in ectothermic vertebrates are discussed.